A STUDY ON EMPLOYEE RETENTION STRATEGIES AND ITS IMPACT ON EMPLOYEE DECISION MAKING PROGRAMS AND SATISFACTION LEVEL AMONG AGRISOFT DAIRY AND AGRO PRODUCER CO. LTD. - DEENA, Dr PRABHA (The journal of contemporary issues in business and government, 2021)
This study analysis the relationship between decision-making and job satisfactionbetween employees in the organization. This study was shown in the form of research on positivism. The study accepted the structure of descriptive research. A sample of 82 Employee was selected, and a questionnaire prepared to collect survey data was distributed. To study the impact on employee decision making programs and satisfaction level among Agrisoft Dairy and Agro products, the study was conducted in Pandalam. Data collected by questionnaire and descriptive analysis and, hypothesis test was conducted. The outcomes indicate that the level of job satisfaction for employees of Agrisoft Dairy and Agro Producer Co.LTD is growing in proportion to the increase in their level of partaking in decision-making.